Comparison of Hematological Levels of Simmental-Ongole Crossbreed (SimPO) and Ongole Crossbreed (PO) Cattle Reared Semi-Intensively - Kristanto, Dwi; Septiyani, Septiyani (Jurnal Medik Veteriner, 2023)
Hematological analysis in cattle is an important basis for determining physiological conditions, biomedical study, and veterinary clinical diagnosis. This study aimed to determine the comparison of hematological values between Simmental-Ongole crossbreed (SimPO) and Ongole crossbreed (PO) cattle reared semi-intensively in oil palm plantations area. A total of 70 blood samples were collected from 35 female SimPO and 35 female PO cattle aged ± 3,5 years who reared from the same area. Blood samples were collected via the coccygeal vein as much as 3 ml, performed at 07.00 in the morning before being grazed on oil palm plantations. Blood samples were collected using a vacutainer tube containing Ethylene Diamine Tetra-Acetic Acid (EDTA) for further analysis using a hematology analyzer. Data from hematological examination results were then analyzed using an independent sample t-test with a significance level of p < 0,05. In results, reported that there were no significant differences in several hematological parameters that have been analyzed. We can conclude that there was no substantial hematological level in the SimPO and PO cattle reared semi-intensively on oil palm plantations.